Headland Bay Beaches and Zeta-Form Beaches as Geo Resources: Morphological Evidence from Sri Lanka - Sachith Gamage; Jinadasa Katupotha (Advances in Technology, 2025)
The term “geo-resources” refers to all geological resources that serve as the basis for life in modern-day society. The beach systems associated with the southwestern and southern coastal zones are well rich in headland bay beaches and zeta-form beaches of different sizes. Among those beaches, beaches are also a significant feature in the selected area from Maggona Head (southwestern coast) to Rekawa Lagoon (southeastern coast). The evolution of these beaches depends on wave forcing and morphological characteristics, and the morphological feature is defined as a beach lying on the leeward side of a headland subjected predominantly to wave attack. These beaches characteristically have a seaward-concave plan shape resulting from erosion caused by refraction, diffraction, and reflection of waves into the shadow zone behind the headland. Tide-induced currents have no direct effect on the plan shape of headland-bay beaches in the area. Various physical changes were observed in the study areas via Google Earth Pro, and historical imagery was used to understand the changes. MepBay software was used to evaluate the stability of the beaches. Aerial images of the bayed beaches were opened via MepBay software, and the following control points were defined manually. According to the findings, the coastline and coastal zone have changed drastically over the years. Coastal infrastructure development and accretion/erosion caused by monsoon wind patterns are the main influences on such changes, and many embayed beaches in the study area are in static equilibrium, but few are in a dynamic equilibrium state. Most beaches are either used for fisheries or for tourism activities. However, since many beaches have the potential to be used as renewable energy sources and biodiversity hotspots, the present study suggests incorporating as many uses as possible into these resources rather than utilizing them for a single purpose. However, proper scientific studies should be conducted prior to commencing such activities to ensure long-term sustainability.